Attack intensity and effectiveness pheromone on Oryctes rhinoceros L. in oil palm, Seluma district, Bengkulu. - Ginting, S.; Ddjamilah; Pryatiningsih; Gusnitha, F. W.; Sariasih, Y.; Tarigan, S. I. (International Journal of Agricultural Technology, 2025)
Oil palm production continues to increase as the area of oil palm plantations increases. Seluma is one of the oil palm production centers in Bengkulu, which is located in the wet tropical region directly bordering the Indian Ocean. One of the main pests on oil palm plants is Oryctes rhinoceros, this pest can cause attacks on immature and mature plants. The use of ferotrap can control O. rhinoceros beetles. However, information regarding O. rhinoceros attacks oil palm has not been reported in Bengkulu. The results showed that the percentage of attacks against the beetle O. rhinoceros was highest in oil palm plantations in Tanjung Seluai Village was 10.53% with an attack intensity was 12.33%, then in Riak Siabun Village the percentage of attacks was 3.09% with an attack intensity was 4.67 % and on oil palm plantations at PT. Sandabi Indah Lestari had no attacks. The lowest average population of O. rhinoceros beetles was 4.67 individuals/ha/2 months in Tanjung Seluai Village, and 7 individuals/ha/2 months in PT. Sandabi Indah Lestari and the highest was 7.67 individuals /ha/2 months in Riak Siabun Village.